Serrated Lesions of Colorectum: A New Pathway in Colorectal Carcinogenesis - Savas Nurten (Journal of Colon And Rectal Cancer, 2015)
Colorectal polyps were traditionally classified as hyperplastic or adenomatous polyps. Adenomatous polyps were thought to be the precursor lesions of most of the colorectal cancers, but later serrated lesions were recognized as precursors of nearly one-third of colorectal cancers. Serrated lesions are a distinct group of polyps with special morphologic and histologic properties and a different carcinogenesis pathway to colorectal cancers. They are pale, flat or depressed lesions which may result in failure of detection on colonoscopy. So the endoscopist should be aware of these lesions and should follow the patients according to the surveillance guidelines.